Measuring Selectivity and Market Timing Performance of Mutual Funds in Indonesia Using Single and Dual Beta Models - Paramita, V S; Sembiring, F M; Safitri, D (KnE Social Sciences, 2018)
This study aims at measuring the performance of mutual funds based on the ability of investment managers in conducting selectivity and market timing by using the Treynor-Mazuy Model. The method used in this study is explanatory survey method or explanatory research. The populations in this study were 167 mutual funds in Indonesia in the period of 2008-2014. Based on purposive sampling criteria, the samples were 29 mutual funds. The data analysis technique used was two-pass regression model. The first pass regression was based on time series data and the second pass regression was based on cross-section. Testing the model was based on single beta model and dual beta model. This study showed that in single beta model, without separating bullish and bearish market conditions, mutual fund investment managers in Indonesia did not have selectivity ability, but had market timing capability. If a dual beta model that separated the bullish and bearish market conditions was used, the difference of the performance of the investment managers was showed. In bullish market condition, mutual fund investment managers in Indonesia did not have selectivity capability but had market timing capability. On the other hand, in bearish market condition, mutual fund investment managers in Indonesia did not have selectivity capability and did not have market timing capability. Keywords: Single and Dual Beta, Selectivity, Market Timing.